Foraging behaviour and diet of American Oystercatchers in a Patagonian intertidal area affected by nutrient loading - García, Germán Oscar; Isacch, Juan Pablo; Laich, Agustina Gómez; Albano, Mariano; Favero, Marco; Cardoni, Daniel Augusto; Luppi, Tomás; Iribarne, Oscar (Emu, 2010)
Eutrophication increases the biomass of opportunistic green macroalgae that covers intertidal zones, and macroalgal blooms may affect the intertidal invertebrate community and predation of invertebrates by shorebirds. In San Antonio Bay, Argentina, eutrophication from the discharge of wastewater from a coastal town produces periodic macroalgal blooms. Our aim was to assess if macroalgal blooms affect the foraging behaviour and diet of the American Oystercatcher (Haematopus palliatus). A macroalgal transplant experiment was performed in order to evaluate how epifaunal species respond to a macroalgal canopy. The availability of prey for Oystercatchers, and their foraging behaviour and diet, were analysed in two paired channels with different nutrient loadings. Oystercatchers generally ate the most profitable prey and avoided prey with a profitability value lower than the mean rate of energy intake. During the macroalgal blooms, Oystercatchers avoided two prey species with high profitability values, shifting their foraging strategy and feeding onto a suboptimal prey but with a high encounter rate. Our results suggest that nutrient loadings and the macroalgal blooms that they generate have effects on the diet and foraging behaviour of Oystercatchers, which results in an increase of the average rate of energy intake of Oystercatchers foraging along the channel subject to a macroalgal bloom.